Optimizing individual stance position in the swim start on the OSB11 - Kibele, A.; Biel, K.; Fischer, S. (BISp-Jahrbuch Forschungsförderung 2012/13, 2013)
Since 2010, the OSB11 starting block model has been used for national and international championships. It provides clear advantages in swim start performance as compared to the previously used OSB9 device (e. g. Honda et al., 2010; Biel et al., 2010). However, there is scarce knowledge on the optimal stance position for swimmers with respect to their individual body length or leg preference (e. g., Slawson et al., 2011; Takeda et al., 2012). For example, Slawson et al. (2011) conducted a study on 32 British elite swimmers analyzing the effects of the stance width (feet placed in tandem position and feet placed shoulder wide in parallel position), the foot rest positions, and the preferred front leg. One of the most striking results in this study was that the optimal stance position on the new OSB11 was different for males and females. For example, these authors showed for the male swimmers that a wide stance width was associated with increases in block time and attenuated horizontal and vertical take-off forces in conjunction with a decreased horizontal take-off velocity. Thus, a narrow stance with a tandem foot position is beneficial for male swimmers. However, for the female swimmers, a wide stance position was associated with increased horizontal take-off forces and decreased absolute and relative flight distances. In a separate, single case study, Slawson and coworkers confirmed that the side preference for the front leg, the stance width, and the wedge position are the most important variables for the stance position on the block. In this study, two thirds of the subjects displayed either improvements or no changes in swim start performances based on stance variations in comparison to their preferred stance configuration. The average improvements in the swim start performance were found to be 0,06 s with extreme values as large as 0,14 s. While these values appear insignificant, a number of Olympic races were won within milliseconds. For example, during the Olympic freestyle races for women in Beijing 2008, Britta Steffen (Germany) won the 100-m-race by 4 ms to Lisbeth Trickett (Australia). For the 50-m-freestyle-race, Britta Steffen won by as little as 1ms to Dara Torres from the USA. Therefore, even it seems worthwhile to analyse the optimal stance configuration for the individual swimmer.